2016
DOI: 10.3390/mi7120231
|View full text |Cite
|
Sign up to set email alerts
|

The High Q Factor Lateral Field–Excited Thickness Shear Mode Film Bulk Acoustic Resonator Working in Liquid

Abstract: A high Q factor film bulk acoustic resonator operating in thickness shear mode excited by a lateral field is described in this paper. The influence of electrode parameters on the resonator performance is studied by the finite element method. The results showed that three key electrode parameters, including the gap, length and width, played important roles in the optimization of the resonator performance. The highest Q factor of up to 643 was obtained when the parallel electrodes were designed to be 100 µm × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Higher order modes of the Lamb waves rather than the S 0 modes can achieve better sensitivity for applications due to their high phase velocity, low phase velocity dispersion, and lower impedance. 149 Tao et al 140 reported a flexible ZnO/Al acoustic device that can excite both the lamb wave mode and LFE-TSM mode individually at their resonant frequencies, enabling to perform sampling, patterning, and biosensing selectively in a single device. Lamb waves were excited for sample dilution and transport by adjusting the input SAW power, while the LFE-TSM waves enabled particles patterning by agitating fundamental orders with low input power as well as biosensing by monitoring the frequency shifts for higher order waves (Fig.…”
Section: Flexible Saw Devices Based On the Lamb Wavementioning
confidence: 99%
“…Higher order modes of the Lamb waves rather than the S 0 modes can achieve better sensitivity for applications due to their high phase velocity, low phase velocity dispersion, and lower impedance. 149 Tao et al 140 reported a flexible ZnO/Al acoustic device that can excite both the lamb wave mode and LFE-TSM mode individually at their resonant frequencies, enabling to perform sampling, patterning, and biosensing selectively in a single device. Lamb waves were excited for sample dilution and transport by adjusting the input SAW power, while the LFE-TSM waves enabled particles patterning by agitating fundamental orders with low input power as well as biosensing by monitoring the frequency shifts for higher order waves (Fig.…”
Section: Flexible Saw Devices Based On the Lamb Wavementioning
confidence: 99%
“…the thickness‐extensional mode (TE), since c ‐axis ZnO was used for the PZE layer. The shear mode gets generated in two cases; by lateral excitation, in which we align both the electrodes parallel to the PZE film surface or by depositing the c ‐axis tilted ZnO film as a PZE layer, both of these are not the case here [10 ]. In addition to the modal analysis, the harmonic analysis was done to obtain the impedance characteristic and the quality factor ( Q ) of FBAR.…”
Section: Device Structure and Simulationmentioning
confidence: 99%
“…Among these four materials, AlN has the highest acoustic wave velocity and excellent thermal conductivity [ 15 , 16 ]. Therefore, various AlN-based resonators have been reported, such as flexural mode resonators [ 17 ], film bulk acoustic wave resonators (FBAR) [ 18 ], contour mode resonators [ 19 ], and lamb wave resonators [ 20 ]. Different modes have different frequency ranges; for contour mode, the main frequency is around 10 MHz to 10 GHz, while that of flexural mode is often smaller than 10 MHz.…”
Section: Introductionmentioning
confidence: 99%